Humoral and cellular immunogenicity of homologous and heterologous booster vaccination in Ad26.COV2.S-primed individuals: Comparison by breakthrough infection - Hyun, Hakjun; Jang, A-Yeung; Park, Heedo; Heo, Jung Yeon; Seo, Yu Bin; Nham, Eliel; Yoon, Jin Gu; Seong, Hye; Noh, Ji Yun; Cheong, Hee Jin; Kim, Woo Joo; Yoon, Soo-Young; et al. (Frontiers in Immunology, 2023)
Background: Whether or not a single-dose Ad26.COV2.S prime and boost vaccination induces sufficient immunity is unclear. Concerns about the increased risk of breakthrough infections in the Ad26.COV2.S-primed population have also been raised. Methods: A prospective cohort study was conducted. Participants included healthy adults who were Ad26.COV2.S primed and scheduled to receive a booster vaccination with BNT162b2, mRNA-1273, or Ad26.COV2.S. The IgG anti-receptor binding domain (RBD) antibody titers, neutralizing antibody (NAb) titers (against wild type [WT] and Omicron [BA.1 and BA.5]), and Spike-specific interferon-γ responses of the participants were estimated at baseline, 3–4 weeks, 3 months, and 6 months after booster vaccination. Results: A total of 89 participants were recruited (26 boosted with BNT162b2, 57 with mRNA-1273, and 7 with Ad26.COV2.S). The IgG anti-RBD antibody titers of all participants were significantly higher at 6 months post-vaccination than at baseline. The NAb titers against WT at 3 months post-vaccination were 359, 258, and 166 in the participants from the BNT162b2-, mRNA-1273-, and Ad26.COV2.S-boosted groups, respectively. Compared with those against WT, the NAb titers against BA.1/BA.5 were lower by 23.9/10.9-, 16.6/7.4-, and 13.8/7.2-fold in the participants from the BNT162b2-, mRNA-1273-, and Ad26.COV2.S-boosted groups, respectively, at 3 months post-vaccination. Notably, the NAb titers against BA.1 were not boosted after Ad26.COV2.S vaccination. Breakthrough infections occurred in 53.8%, 62.5%, and 42.9% of the participants from the BNT162b2-, mRNA-1273-, and Ad26.COV2.S-boosted groups, respectively. No significant difference in humoral and cellular immunity was found between individuals with and without SARS-CoV-2 breakthrough infections. Conclusion: Booster vaccination elicited acceptable humoral and cellular immune responses in Ad26.COV2.S-primed individuals. However, the neutralizing activities against Omicron subvariants were negligible, and breakthrough infection rates were remarkably high at 3 months post-booster vaccination, irrespective of the vaccine type. A booster dose of a vaccine containing the Omicron variant antigen would be required.